2007
DOI: 10.1194/jlr.m600486-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Further biochemical characterization of human pancreatic lipase-related protein 2 expressed in yeast cells

Abstract: Recombinant human pancreatic lipase-related protein 2 (rHPLRP2) was produced in the protease Adeficient yeast Pichia pastoris. A major protein with a molecular mass of 50 kDa was purified from the culture medium using SP-Sepharose and Mono Q chromatography. The protein was found to be highly sensitive to the proteolytic cleavage of a peptide bond in the lid domain. The proteolytic cleavage process occurring in the lid affected both the lipase and phospholipase activities of rHPLRP2. The substrate specificity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 36 publications
2
69
1
Order By: Relevance
“…This characterization is critical for interpreting any results in mice because the kinetics of PLRP2 varies considerably among species. For instance, human PLRP2 (hPLRP2) has almost no activity in the presence of bile salt micelles and is not reactivated by colipase (10)(11)(12). The same is true for horse PLRP2 ( 13 ).…”
Section: Protein Extraction and Western Blotmentioning
confidence: 60%
See 2 more Smart Citations
“…This characterization is critical for interpreting any results in mice because the kinetics of PLRP2 varies considerably among species. For instance, human PLRP2 (hPLRP2) has almost no activity in the presence of bile salt micelles and is not reactivated by colipase (10)(11)(12). The same is true for horse PLRP2 ( 13 ).…”
Section: Protein Extraction and Western Blotmentioning
confidence: 60%
“…The same is true for horse PLRP2 ( 13 ). It has been suggested that the major physiological role of hPLRP2 is as a galactolipase ( 10,12,14,15 ). In contrast, rat PLRP2 has activity in the presence of bile salt micelles even in the absence of colipase.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 67%
See 1 more Smart Citation
“…PTL functions in the presence of colipase in the hydrolysis of emulsified fats in the small intestine following secretion from the pancreas [1][2][3][4][5]; PLR1 is also found in pancreatic secretions but has an as yet unknown function and exhibits no detectable triacylglycerol, cholesterol ester or galactolipase activities [6,8]; PLR2 functions as a pancreatic secretion galactolipase but may also contribute to T cell cytotoxicity in the body [6,25,65]; while PLR3 serves a related, but as yet unknown, lipase function.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and biochemical studies of mammalian PLR2 have reported strong similarities with PTL although differences were observed in kinetic and colipase binding properties and significant species differences were also reported [4][5][6][7][23][24][25]. Significantly, this enzyme has been shown to be predominantly responsible for pancreatic lipase-like neonatal fat digestion in rats and mice [26] and participates in the dietary fat digestion in human newborn children [27,28].…”
Section: Introductionmentioning
confidence: 99%